THE ROLE OF EDUCATION IN THE FORMATION OF CIVIL SOCIETY - Lamara Kadagidze (European Scientific Journal, ESJ, 2016)
Georgia has gone through a significant transformation in a recent decade and the educational sector is one of the many that has undergone considerable reforms. In an attempt to modernize and to bring it more in line with European and American standards the Georgian government adopted a national accreditation program and began tackling corruption in the sector. Societal involvement and a consensus-based agreement on general principles became of vital importance for the development of Georgia’s higher education system. Citizens who actively participate in their nation’s public affairs play perhaps the most important role in a vibrant democracy. An informed and engaged citizenry provides both a check on government power and valuable feedback the government can use to become more responsive. During the Soviet era, independent civic initiative was stifled and citizens were encouraged to believe that the state had the sole responsibility for providing for its citizens. Since the “Rose Revolution,” there has been a renewed sense of civic pride, but this was demonstrated more in nationalist awareness than civic activism. Georgians have never been shy to take to the streets in demonstrations to express dissatisfaction with the government and this was considered to be the only means of civic participation. However, the summer flood 2015 manifested a completely new era of the commitment of Georgian youth to participatory democracy. The article highlights the case of how Georgian citizens (mostly youth with the academic background they obtained owing to the reformed west-oriented education system of Georgia) effectively engaged with other citizens (national and foreign) and set an example for the government to influence public policy and ensure greater socio-cultural responsiveness. Thus, proving that Georgia can score higher in socio-cultural environment encompassing elements like propensity to participate, trust and giving and volunteering, since these elements are fundamental to the development of a consolidated civil society.